PENERAPAN MODEL COOPERATIVE LEARNING TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM (IPA) KELAS V SEKOLAH DASAR 03 ELLA HULU - ., Apriadi; Kristiani, Sri Wahyuni; Wibowo, Deki (STKIP Melawi, 2015)
Abstract: The main purpose of this research is to apply the model of CooperativeLearning of type Numbered Heads Together (NHT) in order to improve studentlearning performance in natural science subject in fifth gradeat Public ElementarySchool 03 Ella Hulu, MenukungSub-District, Melawi Regency, Year 2013/2014. Themethod of this research was Classroom Action Research by using observation andtest as data collection techniques. The research instrument used was observation sheetand written test. Based on the observation sheet, on the first cycle the improvement ofstudents’ performance achieved 59,21%, whileon the second cycle the value obtained80.26% and graded as ‘very good’. On the other hand, the success criteria of thestudents' learning result of the first cycle was 65.84%, while on the second cycle, thelearning result reached 100%. In conclusion, applying Cooperative Learning model oftype Numbered Heads Together (NHT) to Natural Science subject in fifth grade atElementary School 03 Ella Hulu, Menuking Sub-District, Melawi Regency hasresulted in the increasing of student performance.Keywords: Type Numbered Heads Together (NHT), Natural Science Study Resultsin Elementary SchoolAbstrak: Tujuan utama penelitian ini adalah untuk melakukan penerapan modelCooperative Learning Tipe Numbered Heads Together (NHT) agar dapatmeningkatkan hasil belajar siswa pada mata pelajaran IPA kelas V SDN 03 Ella HuluKecamatan Menukung Kabupaten Melawi Tahun Ajaran 2013/ 2014. Metodepenelitian ini adalah penelitian tindakan kelas dengan teknik pengumpulan data yakniobservasi dan tes. Instrumen penelitian yang digunakan lembar observasi dan testertulis. Hasil Peningkatan lembar observasi siswa siklus I diperoleh 59,21%, padasiklus II diperoleh 80,26% dengan kategori sangat baik, sementara kriteriakeberhasilan tindakan hasil belajar siswa siklus I diperoleh 65,84%, siklus II hasilbelajar diperoleh 100% sehingga hasil belajar siswa dengan melakukan penerapanmodel cooperative learning tipe numbered heads together (NHT) pada pembelajaranIlmu Pengetahuan Alam (IPA) Kelas V Sekolah Dasar Negeri 03 Ella HuluKecamatan Menukung Kabupaten Melawi menjadi meningkat.Kata Kunci : Tipe Numbered Heads Together (NHT), Hasil Belajar IPA di SD.